Keteladanan dalam Memimpin: Studi Kasus Kepemimpinan Transformasional dan Organizational Citizenship Behavior pada Startup - Liza Yudhita Widyastuti (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2026)
This research employs a case study approach on Startup X as the researcher's client organization. In this case, researcher as organization psychological consultant which helped them in the human resources aspect to improve their business. Startup X was well known because of their founder's inspirational story. Therefore this study aims to examine the relationship between the transformational leadership dimensions and organisational citizenship behaviour (OCB) in this organization. Researcher used a mixed-method with total sampling, involving 21 employees for quantitative data, 3 employees and 2 management members for initial and then triangulation of the result. To measure transformational leadership dimensions, this study utilized the Multifactor Leadership Questionnaire Form 5x (MLQ 5x) developed by Avolio and Bass (1995). Meanwhile, OCB was measured by Organisational Citizenship Behaviour Checklist (OCB-C), developed by Spector and Fox (2011). The Spearman correlation result showed there is a significant relationship between idealised influence and OCB in Startup X (r = 0.504, p = 0.02). This finding contributes to the digital startup business context by demonstrating higher levels of leader’s inspirational behavior, reflected in increased employees’ voluntary extra-role behaviours.